2020
DOI: 10.3390/insects11100716
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Entomopathogenic Fungi to Chrysoperla externa (Neuroptera: Chrysopidae)

Abstract: We aimed to evaluate the selectivity of entomopathogenic fungi to larvae of Chrysoperla externa (Neuroptera: Chrysopidae). For this purpose, Beauveria bassiana (strain ESALQ PL63), Metarhizium anisopliae (strain ESALQ E9) and Metarhizium rileyi (strain UFMS 03) were assessed at different concentrations (1 × 107, 1 × 108 and 1 × 109 conidia mL−1). The control treatment consisted of distilled water and Tween80 0.01. The treatments were applied with a Potter spray tower using two different methodologies: direct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Recently, Macedo et al (2020) discussed the possibilities of disseminating B. basssiana spores by bees during coffee blooming and its contributition to the regulation of CBB populations. The main advantages of using Beauveria formulations are their low toxicity to workers and low impact on some beneficial insects (Mingotti Dias et al, 2020), but their high cost and variable efficiency should be considered. Finally, is worth to mention that the propagule viability and infection of B. bassiana on CBB are favored in coffee plantations under managed shade compared to full sun exposure, possibly due to the interception of solar radiation and higher humidity (Edgington et al, 2000;Turro et al, 2013;Mariño et al, 2016).…”
Section: Biopesticidesmentioning
confidence: 99%
“…Recently, Macedo et al (2020) discussed the possibilities of disseminating B. basssiana spores by bees during coffee blooming and its contributition to the regulation of CBB populations. The main advantages of using Beauveria formulations are their low toxicity to workers and low impact on some beneficial insects (Mingotti Dias et al, 2020), but their high cost and variable efficiency should be considered. Finally, is worth to mention that the propagule viability and infection of B. bassiana on CBB are favored in coffee plantations under managed shade compared to full sun exposure, possibly due to the interception of solar radiation and higher humidity (Edgington et al, 2000;Turro et al, 2013;Mariño et al, 2016).…”
Section: Biopesticidesmentioning
confidence: 99%
“…Similar results were found bySayed et al (2021) who studied the side effects of B. bassiana against C. undecimpunctata and Hippodamia variegate and reported that C. undecimpunctata and H. variegata remain unaffected by the presence of B. bassiana, as no significant changes have been documented. Also,Dias et al (2020) noted a low mortality rate among Ch. externa larvae treated with Buvariae.…”
mentioning
confidence: 97%